Rho kinase inhibitors ameliorate cognitive impairment in a male mouse model of methamphetamine-induced schizophrenia - Jingzhu Liao; Geyao Dong; Wenjun Zhu; Bolati Wulaer; Hiroyuki Mizoguchi; Masahito Sawahata; Yue Liu; Kozo Kaibuchi; Norio Ozaki; Toshitaka Nabeshima; Taku Nagai; Kiyofumi Yamada (Pharmacological Research, 2023)
Schizophrenia (SCZ) is a severe psychiatric disorder characterized by positive symptoms, negative symptoms, and cognitive deficits. Current antipsychotic treatment in SCZ improves positive symptoms but has major side effects and little impact on negative symptoms and cognitive impairment. The pathoetiology of SCZ remains unclear, but is known to involve small GTPase signaling. Rho kinase, an effector of small GTPase Rho, is highly expressed in the brain and plays a major role in neurite elongation and neuronal architecture. This study used a touchscreen-based visual discrimination (VD) task to investigate the effects of Rho kinase inhibitors on cognitive impairment in a methamphetamine (METH)–treated male mouse model of SCZ. Systemic injection of the Rho kinase inhibitor fasudil dose-dependently ameliorated METH-induced VD impairment. Fasudil also significantly suppressed the increase in the number of c-Fos–positive cells in the infralimbic medial prefrontal cortex (infralimbic mPFC) and dorsomedial striatum (DMS) following METH treatment. Bilateral microinjections of Y-27632, another Rho kinase inhibitor, into the infralimbic mPFC or DMS significantly ameliorated METH-induced VD impairment. Two proteins downstream of Rho kinase, myosin phosphatase-targeting subunit 1 (MYPT1; Thr696) and myosin light chain kinase 2 (MLC2; Thr18/Ser19), exhibited increased phosphorylation in the infralimbic mPFC and DMS, respectively, after METH treatment, and fasudil inhibited these increases. Oral administration of haloperidol and fasudil ameliorated METH-induced VD impairment, while clozapine had little effect. Oral administration of haloperidol and clozapine suppressed METH-induced hyperactivity, but fasudil had no effect. These results suggest that METH activates Rho kinase in the infralimbic mPFC and DMS, which leads to cognitive impairment in male mice. Rho kinase inhibitors ameliorate METH-induced cognitive impairment, perhaps via the cortico-striatal circuit.